2015
DOI: 10.1177/1077800415614033
|View full text |Cite
|
Sign up to set email alerts
|

The Naked Wind Turns/the Corner in Surprise

Abstract: This article constitutes a narrative of the life events of Antonio, a man belonging to the Roma community. His life story combines passages of exclusion, in which Antonio was the target of cultural bias that even led him to be imprisoned, with transformative experiences that were greatly influenced by his participation in a Dialogic Literary Gathering. Through the shared reading of Federico García Lorca’s Gypsy Ballads, he strengthened his identity as a man who is deeply proud of belonging to the Roma communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
6
0
3
Order By: Relevance
“…This is possible through the egalitarian dialogue by both parties. Thus, the researcher will use all the methodological tools to give a voice to minority groups (Munté, 2015). When research on minority groups ignores their voices, biased conclusions that blame these groups for the inequalities they suffer may arise.…”
Section: Methodsmentioning
confidence: 99%
“…This is possible through the egalitarian dialogue by both parties. Thus, the researcher will use all the methodological tools to give a voice to minority groups (Munté, 2015). When research on minority groups ignores their voices, biased conclusions that blame these groups for the inequalities they suffer may arise.…”
Section: Methodsmentioning
confidence: 99%
“…DLGs break the social stereotype that non-academic people cannot read, enjoy and debate classic literature (Torras- Gómez et al, 2021).With the creation of DLGs, Flecha and adult participants with no academic studies showed that dialogue is a key to social transformation. Roma participants like Antonio, whose story will be shared later, show that engaging in dialogues that connect the best literary works with their own life experiences and sentiments contributes to crafting desired futures for themselves and their families (Aubert, 2015;Munté, 2015), despite concepts such as habitus which hinder their educational and social success.…”
Section: Dlgs Defying Determinism During the Spanish Transition To Democracymentioning
confidence: 99%
“…TRANSFORMAR VIVIENDO LA LITERATURA La mayoría de participantes de las primeras TLD, así como muchos y muchas que actualmente participan en ellas, no tienen estudios universitarios, en muchos casos ni siquiera el bachillerato, y algunos y algunas son analfabetas o neolectores en el momento de comenzar a participar en las tertulias (Álvarez et al, 2018;García Yeste et al, 2017a;Munté, 2015). A muchos y muchas, antes de participar en las tertulias, las estructuras sociales y corrientes posmodernas les hicieron creer que no podrían continuar sus estudios.…”
unclassified
“…Como ilustran los y las autoras, las reflexiones compartidas de las vidas y trayectorias personales de las participantes y la toma de conciencia de sus oportunidades para mejorarlas las anima a soñar más allá de los muros (Alvarez et al, 2018). En una línea similar, Munté (2015) describe la vida de Antonio, un gitano que, en algunos de los momentos más duros de su vida, la mayoría de ellos impulsados por prejuicios contra las personas gitanas, encontró un sentido en las TLD para mantener vivos sus sueños. La autora describe en palabras de Antonio un momento en el que un conocido lo traicionó y lo enredó en problemas legales e, incluso después de que ese conocido admitiera la inocencia de Antonio, fue enviado a prisión (Munté, 2015).…”
unclassified
See 1 more Smart Citation